Endocrine Hypertension 2012
DOI: 10.1007/978-1-60761-548-4_14
|View full text |Cite
|
Sign up to set email alerts
|

Central Mineralocorticoid Receptors and Cardiovascular Disease

Abstract: sodium and water by the kidneys [8] became commonly accepted as solely responsible for the hypertension produced by mineralocorticoid + salt excess. Mineralocorticoid Receptors in the Brain Mediate Hemodynamic EffectsThe demonstration of specific binding of aldosterone in select areas of the brain, as well as the heart and vessels [9] , and the finding that the ablation of the anteroventral area of the third ventricle abrogated mineralocorticoid + salt, renovascular and Dahl salt-sensitive (SS) rat hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 219 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…Furthermore it was demonstrated that individuals with RHT without primary hyperaldosteronism have higher aldosterone levels than normal population [22]. The adverse effect of aldosterone excess causes sympathetic activation by stimulation of mineralocorticoid receptors in the paraventricular nuclei [23]. The effects of an over-activated sympathetic nervous system on the haemostatic system occur in two ways.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore it was demonstrated that individuals with RHT without primary hyperaldosteronism have higher aldosterone levels than normal population [22]. The adverse effect of aldosterone excess causes sympathetic activation by stimulation of mineralocorticoid receptors in the paraventricular nuclei [23]. The effects of an over-activated sympathetic nervous system on the haemostatic system occur in two ways.…”
Section: Discussionmentioning
confidence: 99%
“…Autoradiographic studies have demonstrated a distinctive pattern of binding of aldosterone in the brain, including in those areas identified by ablation studies to be crucial for the development of mineraolcorticoid excess hypertension 9–11 . The chronic administration of aldosterone into the lateral ventricle (i.c.v.)…”
Section: Effect Of Mineralocorticoids In the Cnsmentioning
confidence: 99%
“…Ablation (KO) of limbic (forebrain) mineralo-and glucocorticoid receptors (MR/GR)-which have been associated with depressive states clinically-increase the experimental vulnerability toward stress-induced depression with subsequent sympathetic inhibition and increased parasympathetic (X) tone with systemic and cardiac catecholamine (nor-/epinephrine) depletion and elevated ventricular tachycardias (VTs). This finding may explain increased mortality of heart failure patients suffering from depression and the ineffectiveness of psycho-and pharmacological anti-depressive therapy regarding outcome in the absence of the forebrain MR/GR, a crucial role of the forebrain MR in survival of the acute phase of cardiac ischemia has been observed in rats [18]. Moreover, elevated CS levels are independently associated with mortality in patients suffering from HF [32].…”
Section: Ablation Of the Forebrain Mr/gr Causes Catecholamine Depleti...mentioning
confidence: 95%